Use of earthworm meal with vermi-humus in diet for laying quail - Nazeri, Rebaz; Esmaielzadeh, Ladan; Karimi-Torshizi, Mohammad-Amir; Seidavi, Alireza; Zangeronimo, Marcio Gilberto (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the effect of dietary earthworm (Eisenia fetida) meal (EW), associated with vermi-humus (VH), on the performance, egg characteristics, immunity, and blood constituents of laying quails. A total of 336 female quails (163.94±1.5 g), with 30 days of age, was distributed in 7 treatments and 4 replicates of 12 birds during 42 days. The following treatments were evaluated: control diet without the inclusion of VH and EW; diet with the inclusion of only 0.8% VH; and diets with 0.8% VH supplemented with different EW levels (0.5, 1.0, 1.5, 2.0, and 2.5%). A greater body weight, weight gain, and feed intake were obtained with 1.5% EW; a higher egg productivity, with 0.5–1.0% EW; and a higher egg mass, with 0.5% EW. The inclusion of 2.5% EW reduced eggshell weight and thickness. Levels of 1.0–2.0% EW decreased malondialdehyde in the eggs, whereas 2.0% EW reduced cholesterol content. Higher blood cell volume and antibody titer were obtained with 1.0% EW, whereas higher total protein, globulin, and calcium were obtained with 0.5% EW. Levels of 1.0–1.5% EW + 0.8% VH improve egg production and characteristics, as well as the humoral response of quails, whose performance is not affected.